The antibiotic PSX-1 produced by Penicillium stipitatum is identical with botryodiplodin - Fuska, J; Proksa, B; Uhrín, D (Folia microbiologica, 1988)
Antibiotic PSX-1 exhibiting antitumour activity, formerly isolated from the filtrate of a culture of Penicillium stipitatum, was shown to be identical with botryodiplodin.
Keywords: Chemical Phenomena; protinádorová antibiotika; Antibiotics, Antineoplastic; chemické jevy; furany; Chemistry; Penicillium; chemie; Furans